Genetically Predicted Higher Educational Attainment Decreases the Risk of COVID-19 Susceptibility and Severity: A Mendelian Randomization Study - Jian, Zhongyu; Wang, Menghua; Jin, Xi; Wei, Xin (Frontiers in Public Health, 2021)
Background: Prior observational studies indicated that lower education attainment (EA) associated with higher COVID-19 risk while these findings were vulnerable to bias from confounding factors or reverse causation. We aimed to clarify the causal effect of EA on COVID-19 susceptibility, hospitalization, and severity using Mendelian randomization (MR). Methods: We identified genetic instruments for EA from a large genome wide association study (GWAS) (N = 1,131,881). Summary statistics for COVID-19 susceptibility (14,134 cases and 1,284,876 controls), hospitalization (6,406 cases and 902,088 controls), and severity (3,866 cases and 622,265 controls) were obtained from the COVID-19 Host Genetics Initiative. We used single-variable MR (SVMR) and multi-variable MR (MVMR) controlling intelligence, income, body mass index (BMI), vigorous physical activity, sedentary behavior, smoking, and alcohol consumption to estimate the total and direct effects of EA on COVID-19 outcomes. Inverse variance weighted was the primary analysis method. All the statistical analyses were performed using R (version: 4.0.0). Results: Results from SVMR showed that genetically predicted higher EA was correlated with a lower risk of COVID-19 susceptibility (OR 0.81, 95%CI 0.73-0.89), hospitalization (OR 0.53, 95%CI 0.44-0.63), and severity (OR 0.44, 95%CI 0.34-0.56). EA maintained its effects in most of the MVMR, while its association with COVID-19 susceptibility (OR 0.98, 95% CI 0.83-1.16), hospitalization (OR 0.71, 95%CI 0.54-0.93), and severity (OR 0.54, 95%CI 0.37-0.77) was partially attenuated when controlling BMI. Conclusions: EA is a predictor for susceptibility, hospitalization, and severity of COVID-19 disease. Population with lower EA should be provided with a higher prioritization to public health resources to decrease the morbidity and mortality of COVID-19.